DESENVOLVIMENTO DE RECURSOS DIDÁCTICOS INFORMATIZADOS NO ÂMBITO DA EDUCAÇÃO PARA O DESENVOLVIMENTO SUSTENTÁVEL. O EXEMPLO DO COURSEWARE SeRe - Patrícia Sá; Cecília Guerra; Isabel P. Martins; Maria João Loureiro; Rui Vieira; António Pedro Costa; Luís Paulo Reis (Revista Eureka sobre Enseñanza y Divulgación de las Ciencias, 2010)
The lack of courseware for Sciences' teaching and learning in Primary School level, conceived according to Education for Sustainable Development (EDS) approach, was the reason that determined the organisation of a multidisciplinary team with different competences (on Science Education, Educational Technology and Design) for the development of the Courseware Sere "The Human Being and natural resources". Adjusting some principles of software's development, as far as User Centred Design (UCD) is concerned (Costa, Loureiro, Reis, Sá, Guerra e Vieira, 2009; Guerra, 2007),as well as EDS approach (Sá, 2008) and science education perspectives (Cachapuz,Sá-Chaves e Paixão, 2004), the multidisciplinary team collaboratively developed the digital educational resource, which integrated several software typologies within the educational activities. A full presentation of the development process of this digital educational resource will be done throughout this paper.